The Author's View of the Novel â€œHayyaâ€ By Helvy Tiana Rosa and Benny Arnas (A Study of Genetic Structuralism): PANDANGAN PARA PENGARANG TERHADAP NOVEL â€œHAYYAâ€ KARYA HELVY TIANA ROSA DAN BENNY ARNAS : KAJIAN STRUKTURALISME GENETIK - Khaerun Nisa Nuur; Marwati; Rezky Ananda (Universitas Islam Negeri Alauddin, 2022)
This article describes the views of the authors on the novel Hayya by Helvy Tiana Rosa. This research is a sociology of literature research using the theory of Genetic Structuralism by Lucien Goldman. This study uses a qualitative approach. In this study using data collection and analysis techniques in the form of determining the research title, collecting the required materials, reading data and analyzing, writing and compiling. The results of the research are the views of the authors on the novel Hayya by Helvy Tiana Rosa and Benny Arnas which includes humanity and love in it. The novel contains a story about concern for the conflict that occurred in Palestine, a touching and funny story.